Atopic Dermatitis Endotypes: Molecular Pathways and Precision Treatment Strategies - Alobead, Zeiad Abdulaziz; AlMesfer, Asem; Assiri, Ahmad (Journal of Neonatal Surgery, 2021)
Background: Atopic dermatitis (AD) is a complex, heterogeneous inflammatory skin disease. Traditional phenotype-based management often fails to control moderate-to-severe disease, highlighting the limitations of a "one-size-fits-all" approach. A paradigm shift toward a mechanistically-driven understanding, centered on the concept of disease endotypes, is crucial for advancing care. Objective: This review synthesizes the current evidence on major AD endotypes, their defining molecular pathways, and the precision treatment strategies they inform. Methods: The databases were searched for articles published in English in 3 data bases [PubMed – Google scholar- science direct] and a comprehensive analysis of the literature was conducted, focusing on studies that utilized high-throughput 'omics' technologies, genetic associations, and clinical trial data to deconstruct AD pathophysiology. The review delineates endotypes based on distinct molecular signatures and links these drivers to emerging targeted therapies. Conclusion: The stratification of AD into molecular endotypes is foundational to precision dermatology. Moving beyond clinical phenotypes to define the underlying pathological drivers enables the selection of optimal targeted therapies, such as biologics and small molecules, leading to improved efficacy and personalized patient management. Future research must focus on validating practical biomarkers for routine endotype identification in clinical practice.